Helminth Infection Increases the Probability of Indeterminate QuantiFERON Gold in Tube Results in Pregnant Women. (19th February 2014) - Gebreegziabiher, Dawit; Desta, Kassu; Howe, Rawleigh; Abebe, Markos
Abstract : Background. Approximately one-third of the world population is infected with M. tuberculosis and helminths (Kariminia et al. (2009), Walson et al. (2010)). Pregnancy and Helminth infection are known to suppress the T H 1 response (Kariminia et al. (2009), Elias et al. (2006)) on which the QuantiFERON Gold in Tube (QFT-GIT) assay, that measures the released IFN-γ upon in vitro stimulation with mycobacterial antigens, relies on (Thomas et al. (2010)). Objective. To determine whether QFT-GIT indeterminate result is significantly associated with helminth infection or not. Methods. In this cross-sectional study, eighty-five pregnant mothers were screened for parasitic and LTBI using Kato-Katz and QFT-GIT test-respectively, Result. The prevalence of helminth infection in pregnant mothers was 23 (27%) of this 17 (20%) was due to Schistosoma mansoni . Among the total of 85 study participants 26.8% were QFT-GIT positive and 14 (17%) had indeterminate results. Three samples (21.4%) were randomly selected from the indeterminate QFT-GIT results and retested to check the reproducibility of the assay and remained indeterminate. QFT-GIT indeterminate result showed significant association with helminth infection. Conclusion. Helminth infections were significantly associated with indeterminate QFT-GIT results in pregnant mothers. Therefore further study is important to evaluate the possible effect of helminth infection by excluding the effect of pregnancy, as pregnancy also downregulates cellular immunity.